Strengthening the Governance of Regional Development Control and Evaluation Through the Integration of Development Information Systems in Balikpapan City - Istiqomah Istiqomah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Control and evaluation of regional development play an important role in supporting the effectiveness of development planning and decision-making by local governments. However, the implementation of development control in the Balikpapan City Government still faces various obstacles because development data management is carried out through several partially integrated systems, namely the Integrated Performance Evaluation and Accountability Measurement System (REAKSI), the Balikpapan City Budget Realization Reporting Information System (SIPERANGKO), and the Balikpapan One Data Portal. This condition results in repeated data entry, inconsistencies between systems, and the suboptimal use of development evaluation data in the policy-making and regional development planning processes. This policy paper aims to formulate policy recommendations for strengthening the governance of regional development control and evaluation through the integration of development information systems in Balikpapan City. The method used is a qualitative descriptive approach through regulatory review, theoretical review, gap analysis of existing conditions, and policy alternative analysis using the Bardach and Patashnik approach. The results of the study indicate that the most feasible policy alternative is the integration of the REAKSI and SIPERANGKO applications into an Integrated Regional Development Control and Evaluation System, which is expected to improve the integration of development data, reporting efficiency, and the quality of data-based regional development planning.